Analysis of research status and trends on nano-agricultural application: a bibliometric study - Luo, Xing; Li, Jing; Guo, Song; Yu, Hua; Zeng, Xiangzhong; Zhou, Zijun; Shangguan, Yuxian; He, Mingjiang; Ouyang, Yiting; Chen, Kun; Chen, Zhimin; Qin, Yusheng (Frontiers in Plant Science, 2025)
IntroductionThe rapid global population growth and limitations of traditional agricultural practices have resulted in inadequate nutrient supply. Nano-agricultural technology presents significant potential for enhancing crop growth and resistance, reducing stresses, and providing economic benefits with lower environmental risks.MethodsIn this study, a bibliometric analysis of nano-agricultural applications was conducted using the Web of Science Core Collection, and 2,626 publications from 2000 to 2023 were identified, with an exponential increase in both publications and citations.Results and discussionEuropean and Asian countries and institutions are more actively involved, although USA produces the highest-quality papers. Additionally, this field has evolved through two stages: the first stage (2000-2016) focused on the toxicology of nanomaterials (NMs), while the second stage (2017-present) emphasizes NMs as nanofertilizers to promote crop growth, and as nanoregulators or nanopesticides to enhance crop resistance against biotic stress and abiotic stress. Finally, future research perspectives were also proposed, including the optimalizations of NMs, the investigations of the behavior and bioavailability of NMs driven by rhizosphere and phyllosphere process, interdisciplinary collaboration across various fields, the application of NMs from laboratory to the field, and the long-term environmental behaviors and assessments of NMs in diverse ecosystems. Overall, this bibliometric study provides a valuable reference for understanding the development of this field and pinpointing research frontiers.